Szalony protagonista Eurypidesowego „Orestesa” w komentarzach scholiastów - Czerwińska, Jadwiga; Chiżyńska , Katarzyna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
Madness is a constant motif in ancient literature. It was often used by playwrights, including the three greatest tragedians of the Classical Greece: Aeschylus, Sophocles and Euripides. One of the most interesting plays dealing with issues of madness is Euripidean Orestes. This play has received numerous commentaries written by scholiasts, who described all aspects of the state of mania. The article is devoted to the analysis of madness and the corpus of texts are scholia describing Orestes’ disease. Commentaries allow us to establish a definition of mania, show its sources and describe its various physical and mental symptoms. The material presented in the article shows how interesting the phenomenon of madness was for the scholiasts.